A Comparative Transcriptomic Analysis Reveals Conserved Features of Stem Cell Pluripotency in Planarians and Mammals123. (24th July 2012) - Labbé, Roselyne M.; Irimia, Manuel; Currie, Ko W.; Lin, Alexander; Zhu, Shu Jun; Brown, David D.R.; Ross, Eric J.; Voisin, Veronique; Bader, Gary D.; Blencowe, Benjamin J.; Pearson, Bret J.
Abstract: Many long‐lived species of animals require the function of adult stem cells throughout their lives. However, the transcriptomes of stem cells in invertebrates and vertebrates have not been compared, and consequently, ancestral regulatory circuits that control stem cell populations remain poorly defined. In this study, we have used data from high‐throughput RNA sequencing to compare the transcriptomes of pluripotent adult stem cells from planarians with the transcriptomes of human and mouse pluripotent embryonic stem cells. From a stringently defined set of 4, 432 orthologs shared between planarians, mice and humans, we identified 123 conserved genes that are ≥5‐fold differentially expressed in stem cells from all three species. Guided by this gene set, we used RNAi screening in adult planarians to discover novel stem cell regulators, which we found to affect the stem cell‐associated functions of tissue homeostasis, regeneration, and stem cell maintenance. Examples of genes that disrupted these processes included the orthologs of TBL3, PSD12, TTC27, and RACK1 . From these analyses, we concluded that by comparing stem cell transcriptomes from diverse species, it is possible to uncover conserved factors that function in stem cell biology. These results provide insights into which genes comprised the ancestral circuitry underlying the control of stem cell self‐renewal and pluripotency. STEM Cells 2012;30:1734–1745